Antisense mRNA for NPY-Y1 receptor in the medial preoptic area increases prolactin secretion - Silveira,N.A. (1999)
We investigated the participation of neuropeptide Y-Y1 receptors within the medial preoptic area in luteinizing hormone, follicle-stimulating hormone and prolactin release. Four bilateral microinjections of sense (control) or antisense 18-base oligonucleotides of messenger ribonucleic acid (mRNA) (250 ng) corresponding to the NH2-terminus of the neuropeptide Y1 receptor were performed at 12-h intervals for two days into the medial preoptic area of ovariectomized Wistar rats (N = 16), weighing 180 to 200 g, treated with estrogen (50 µg) and progesterone (25 mg) two days before the experiments between 8.00 and 10:00 a.m. Blockade of Y1 receptor synthesis in the medial preoptic area by the antisense mRNA did not change plasma luteinizing hormone or follicle-stimulating hormone but did increase prolactin from 19.6 ± 5.9 ng/ml in the sense group to 52.9 ± 9.6 ng/ml in the antisense group. The plasma hormones were measured by radioimmunoassay and the values are reported as mean ± SEM. These data suggest that endogenous neuropeptide Y in the medial preoptic area has an inhibitory action on prolactin secretion through Y1 receptors.